Влияние редокс потенциала среды на миграцию фосфора в иловой смеси - Юрченко, В. А.; Смирнов, А. В.; Бахарева, Анна Юрьевна (Технологический центр, Украинский государственный университет железнодорожного транспорта, 2015)
Исследованы характеристики влияния окислительно-восстановительного потенциала среды на процесс биологической очистки сточных вод от фосфатов. Количественные зависимости устанавливали при лабораторном моделировании аэробных и анаэробных условий культивирования иловой жидкости, а также при обследовании действующих очистных сооружений канализации. Установлено, что чем ниже ОВП среды, тем больше фосфатов мобилизуется из ила в водную среду в анаэробных условиях обработки и тем больше фосфатов иммобилизуется из водной среды в ил в аэробных условиях.

The characteristics of the influence of the redox potential of the medium on the process of biological wastewater treatment from phosphates were investigated. The research was aimed at identifying new control actions to intensify wastewater treatment from phosphorus compounds and protect natural water bodies from pollution. The quantitative relationships were determined in the laboratory simulation of aerobic and anaerobic cultivation conditions of sludge liquor, as well as when examining existing sewage treatment facilities. It was found that the lower the redox potential values in the anaerobic wastewater treatment zones, the more intensive the phosphate mobilization from activated sludge into the aqueous medium and, consequently, the more phosphates will be immobilized from the aqueous medium into sludge under aerobic conditions. The obtained quantitative characteristics allow to use the redox potential of wastewater (controlled variable) to manage and intensify the deep removal of phosphorus compounds during biological wastewater treatment.
Influence of redox potential of the medium on phosphorus migration in sludge liquor
Keywords: стоки; активный ил; фосфаты; окислительно-восстановительный потенциал; летучие жирные кислоты; wastewater; activated sludge; phosphates; redox potential; volatile fatty acids